2011
DOI: 10.1080/09540105.2011.575124
|View full text |Cite
|
Sign up to set email alerts
|

Development of highly specific fluorescence immunoassay and enzyme-linked immunosorbent assay for detection of dimethyl phthalate in water samples

Abstract: A direct competitive fluorescence immunoassay (dc-FIA) and a direct competitive enzyme-linked immunosorbent assay (dc-ELISA) for the screening of dimethyl phthalate (DMP) in water samples were developed. The immunoassays utilise polyclonal antibodies against DMP raised in rabbits. The anti-DMP antibodies were linked to horseradish peroxidase (HRP) and fluorescein isothiocyanate (FITC). Under the optimal experimental conditions, the dc-ELISA has a linear working range of 0.1Á2000 ng/ml (R 2 00.993) with a limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 28 publications
3
14
0
Order By: Relevance
“…As shown in Fig. 3, the result indicated that the maximum absorbance was obtained with pH 7.4; it is similar with the result of other immunoassay methods [23,26]. Thus, pH 7.4 PBS buffer solution was chosen for our further study.…”
Section: Influence Of Phsupporting
confidence: 81%
See 4 more Smart Citations
“…As shown in Fig. 3, the result indicated that the maximum absorbance was obtained with pH 7.4; it is similar with the result of other immunoassay methods [23,26]. Thus, pH 7.4 PBS buffer solution was chosen for our further study.…”
Section: Influence Of Phsupporting
confidence: 81%
“…4, the absorbance intensity was maximal with the sodium chloride concentration of 0.15 mol/L. This result was in agreement with our previous works [23][24][25]. Hence, it was chosen as the best concentration of sodium chloride in PBS buffer solution for this assay.…”
Section: Influence Of Ionic Strengthsupporting
confidence: 80%
See 3 more Smart Citations